2013
DOI: 10.1128/cvi.00356-12
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Four Commercially Available Avidity Tests for Toxoplasma gondii-Specific IgG Antibodies

Abstract: Toxoplasma infection in pregnant women may cause congenital toxoplasmosis. Diagnosis of infection is based on serological tests aimed at detecting IgM and IgG antibodies against Toxoplasma gondii. However, IgM antibodies are not an accurate marker for discriminating between acute and latent infection. Detection of residual or persistent IgM may occur months or even years after primary infection, while the IgG avidity test is a rapid means of identifying latent infections in pregnant women who exhibit both IgG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
28
0
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 27 publications
4
28
0
6
Order By: Relevance
“…The Enzygnost assay only detected 16.7% of residual IgM antibodies. Given the presence of positive IgM and IgG antibodies in the first serum sample, a second-intention determination, using the same serum, of IgG avidity (when it is high) enabled confirmation of the infection as chronic (12,(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Enzygnost assay only detected 16.7% of residual IgM antibodies. Given the presence of positive IgM and IgG antibodies in the first serum sample, a second-intention determination, using the same serum, of IgG avidity (when it is high) enabled confirmation of the infection as chronic (12,(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…Ocular toxoplasmosis may be observed in immunocompetent patients (10). The diagnosis of toxoplasmosis is based mainly, but not only, on serological tests for IgG and IgM (11,12). These screening techniques enable the immunological status to be defined and the exposure risk for seronegative subjects to be estimated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, cross-evaluation studies have shown variability in the performances of some well-known commercial assays. [31][32][33] Thus, efforts at improving IgG avidity assays are still needed.…”
Section: 37mentioning
confidence: 99%
“…The avidities of anti-Toxoplasma IgG antibodies were determined by using the Platelia Toxo IgG avidity test (Bio-Rad). Based on the manufacturer's instructions, the avidity indexes were classified as follows: Ͻ0.4, low avidity; 0.4 to Ͻ0.5, intermediate avidity; and Ն0.5, high avidity (high avidity suggests an infection Ͼ20 weeks previously) (13).…”
Section: Methodsmentioning
confidence: 99%